Greek Education in Australia - Tamis, Anastasios (Études helléniques / Hellenic Studies, 2005)
This article provides readers with a well-researched portrait of the Greek experience in Australia. The author describes the various waves of immigration ‘down under’ and how the education system struggled to keep up with the demand. Problems of immigration and identity have forged the Australian Greek community into a stong, well-established group. Nevertheless, the current Australian situation resembles that of Canada and the United States in that second- and third-generation parents and children must adjust to maintain the Greek language and culture as the clientele for Greek education has changed dramatically. The author describes both student and teacher needs within the contemporary context as well as the importance of the Paideia Omogenon Program.